Oxidative stress in melanogenesis and melanoma development - Kamiński, Kacper; Kazimierczak, Urszula; Kolenda, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2022)
Melanoma is the most aggressive skin cancer, with a growing number of incidents worldwide and with no effective cure in a metastatic stage so far. There are several pathways and processes engaged in melanoma pathogenesis that have been extensively explored in recent years. The emerging evidence suggests that oxidative stress (OS) is highly involved in melanin synthesis and melanoma formation. Melanoma is particularly susceptible to OS due to the involvement of melanin synthesis and UV radiation in the generation of reactive oxygen species. Oxidative stress influences melanoma immunity, the metastatic potential of melanoma cells and their resistance to therapy. In malignant melanocytes, the process of melanogenesis is frequently upregulated, suggesting possible therapeutic targets. This review describes the role of OS in melanin synthesis in melanocytes and explains how it affects melanoma cells. Better knowledge about the mechanisms involved in cancer progression may result in the development of better treatment strategies.